MEMAHAMI BIROKRAT SEBAGAI PELAYAN PUBLIK DALAM TINJAUAN KOMUNIKASI ORGANISASI - Ira Lusiawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2019)
It is no longer a public secret if in Indonesia from the beginning until now it always faces serious obstacles from the bureaucracy. The attitude and behavior of bureaucrats also greatly affect the implementation of tasks following the existing situation. In many cases, the attitude of the bureaucrat will influence its behavior. There are three types of bureaucrats: operator, manager, and executive. Executive behavior in the local public bureaucracy in Indonesia has experienced significant changes, especially in recruiting new employees, which is also very much influenced by family law. This means that employee recruitment is intended to accommodate family, relatives or friends with a certain amount of reward. Executive behavior that always wants to add subordinates. Organizational communication becomes important when the behavior of bureaucrats adopts and spreads new values in the organization, especially the organization in providing services to the public.Keywords: Organization Communication, Publik Bureaucracy, Bureaucratic Behavior. Â Â